PEMBUATAN MEJA PROJECTOR SEBAGAI ALAT PENUNJANG PEMBELAJARAN DI KELAS - Berthy Pelasula; Richard A. Ririhena; Alexander A.Patty, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
To carry out the learning process in class for Ambon State Polytechnic students, facilities to support the learning process are needed, such as; The function of the projector is as a place to place the projector above it so that the projected results of the learning material displayed are in a vertical reading position for students. Making a projector tool has several stages, namely: The problem identification stage which is based on the results of the service team's observations, then finding the problem and looking for ways to overcome the problem and providing a solution to the problem. The method used to complete these service activities is experimental in the workplace (workshop). The cost planning stage is adjusting the service activities to the funds available for community service services by the Ambon State Polytechnic. The design stage of the projector tool is using the CATIA program. The stage of making the tool requires teamwork to complete making the projector tool. and the tool testing stage, namely after the projector tool has been completed with the aim of evaluating its work function.